HUKUM ISLAM SEBAGAI SUMBER INSPIRASI DALAM PEMBENTUKAN HUKUM KEKELUARGAAN NASIONAL: SEBUAH TINJAUAN KRITIS - Ramdani, M.Turmizi (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2025)
Islamic Law as a Source of Inspiration in the Formation of National Family Law: A Critical Review Abstract This study aims to examine the role of Islamic law as a source of inspiration in the formation of Indonesia’s national family law. The research employs a qualitative approach using library research methods. Secondary data were collected through a literature review and analysis of legal documents, including Marriage Law No. 1 of 1974 and the Compilation of Islamic Law (Kompilasi Hukum Islam/KHI). The findings indicate that Islamic law has made a significant contribution to regulating key aspects of family law, such as marriage, divorce, inheritance rights, maintenance, and child custody. Nevertheless, its implementation in practice faces several challenges, including differences in interpretation, issues of gender justice, and Indonesia’s cultural diversity. This article emphasizes the importance of harmonizing Islamic law with positive law to create a more just and inclusive family law system, as well as the need for adequate legal education to enhance public understanding of the principles of justice in Islamic law. Keywords: Islamic Law, Family Law, Indonesia, Gender Justice, Legal Harmoniza